Durability Improvement of Pd Core-Pt Shell Structured Catalyst by Porous SiO2 Coating. Issue 10 (30th June 2018) - Aoki, Naoya; Inoue, Hideo; Kawasaki, Hisashi; Daimon, Hideo; Doi, Takayuki; Inaba, Minoru
Abstract : Porous SiO2 coating was investigated to suppress agglomeration of catalyst nanoparticles (NPs) and mitigate ECSA decay of carbon supported Pd core-Pt shell structured catalyst (Pt/Pd/C), which is a promising cathode catalyst for polymer electrolyte fuel cells because of its high Pt utilization and enhanced oxygen reduction reaction (ORR) activity. SiO2 coating was formed onto the catalyst via a sol-gel route using 3-aminopropyltriethoxysilane (APTES) or 3-mercaptopropyltrimethoxysilane (MPTES) as a seed molecule prior to hydrolysis of tetraethoxysilane (TEOS). When APTES with an amino functional group (-NH2 ) was used as the seed, SiO2 was coated not only onto catalyst nanoparticles (NPs), but also onto carbon support. On the contrary, SiO2 was selectively coated onto catalyst NPs when MPTES with a thiol functional group (-SH) was used as the seed. Cyclic voltammetry experiments revealed that -SH functional group much strongly adsorbed onto Pt and Pd surfaces than -NH2 functional group did. SiO2 coating formed by the MPTES seed well suppressed NPs' agglomeration and mitigated ECSA decay with less loading of SiO2 coating, improving durability and ORR mass activity of Pt/Pd/C catalyst even after accelerated durability test performed at 80°C.